INTENSIFICATION OF HEAT TRANSFER FROM THE IC CHIP TO THE HEAT SINK THROUGH THE USE OF NANOFILM THERMOELECTRIC HEAT PUMP - T. A. Ismailov; H. M. Gadjiyev; T. A. Chelushkina; D. A. Chelushkin (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The article considers the to enhance the efficiency the thermoelectric heat pump by making the branches of semiconductor p- and n-type as nanofilms and creating conditions for the emergence of additional thermoeffect between the hot and cold junctions of dissimilar metals that will create a more efficient heat pumps with small dimensions.